Integrating Ethnomathematics in Architectural Heritage: A Case Study of BAT Buildings in Cirebon - Sulistiawati Sulistiawati; Aisya Natania; Zahwa Safinah; Risni Maulidia; Chika Nurmayanti Sukanda; Arif Muchyidin (MASI Mandiri Edukasi, 2025)
This study is the first to analyze the British American Tobacco (BAT) Building in Cirebon through an ethnomathematical perspective as a means of supporting contextual mathematics learning in Indonesia. The research is driven by the need for innovative approaches that integrate local culture into mathematics education. The main objective is to identify and describe mathematical concepts embedded in the architectural design of the BAT Building. A descriptive qualitative method was employed, with data collected through direct observation, photographic documentation, and literature review. The analysis focused on architectural elements such as roofs, windows, doors, and façades to reveal underlying mathematical concepts. The findings indicate that the BAT Building incorporates diverse geometric representations, including spatial forms (rectangular pyramids and triangular prisms), flat shapes (rectangles and semicircles), symmetry, patterns, proportions, and geometric transformations. These results demonstrate that colonial industrial architecture not only serves as a historical and cultural landmark but also as a rich source of ethnomathematical knowledge. The study concludes that integrating architectural heritage into mathematics learning provides an effective contextual approach to enhance students’ understanding of geometry. Furthermore, the findings contribute to the development of culturally based teaching materials and highlight the importance of linking mathematics with history and local wisdom to strengthen meaningful learning experiences.